Prevalence of Class V caries in maxillary and mandibular canines of 3-5-year-old children: A retrospective study - Charanya Suresh; Deepa Gurunathan; S Padmapriya (Wolters Kluwer Medknow Publications, 2022)
Caries in primary teeth are a major health concern in socially disadvantaged populations and may alter the eruption pattern and function of their successor. The aim of the study is to find the prevalence of Class V caries in maxillary and mandibular canines in 3-5-year-old children. A single-centered retrospective study was conducted in a private dental institution, Chennai. The data were collected from the Dental Hospital Management System of Saveetha Dental College (DIAS). A test for significance was done with the help of the Chi-square test. The most prevalent caries in canines of children between the age group of 3 and 5 years were cervical caries or Class V caries. 5, 35,951 patient details that were available in DIAS, and 2,35,841 were details of pedodontic patients, 200 patients who fulfilled the inclusion criteria were analyzed. It was observed that the prevalence of caries on the right maxillary and mandibular canines (80.00%) was higher than the left counterpart (20.00%) of the same arch. Maxillary canines (70.00%) had more prevalence of caries as compared to mandibular canines (30.00%). Caries prevalence on the right maxillary and right mandibular primary canine was higher than their left counterparts. Maxillary primary canines had more prevalence of caries as compared to mandibular primary canines.